Mind-body relationships in elite apnea divers during breath holding: a study of autonomic responses to acute hypoxemia - Laurino, Marco; Menicucci, Danilo; Mastorci, Francesca; Allegrini, Paolo; Piarulli, Andrea; Scilingo, Enzo Pasquale; Bedini, Remo; Pingitore, Alessandro; Passera, Mirko; L'Abbate, Antonio; Gemignani, Angelo (Frontiers in Neuroengineering, 2012)
The mental control of ventilation with all associated phenomena, from relaxation to modulation of emotions, from cardiovascular to metabolic adaptations, constitutes a psychophysiological condition characterizing voluntary breath holding (BH). BH induces several autonomic responses, involving both autonomic cardiovascular and cutaneous pathways, whose characterization is the main aim of this study. Electrocardiogram and skin conductance (SC) recordings were collected from 14 elite divers during three conditions: free breathing (FB), normoxic phase of BH (NPBH) and hypoxic phase of BH (HPBH). Thus, we compared a set of features describing signal dynamics between the three experimental conditions: from heart rate variability features (in time and frequency domains and by using nonlinear methods) to rate and shape of spontaneous SC responses. The main result of the study rises by applying a Factor Analysis to the subset of features significantly changed in the two BH phases. Indeed, the Factor Analysis allowed to uncover the structure of latent factors which modeled the autonomic response: a factor describing the autonomic balance, one the information increase rate, and a latter the central nervous system driver. The BH did not disrupt the FB factorial structure, and only few features moved among factors. Factor Analysis indicates that during BH i) only the SC described the emotional output, ii) the sympathetic tone on heart did not change, iii) the dynamics of interbeats intervals showed an increase of long range correlation that anticipates the HPBH, followed by a drop to a random behavior. In conclusion, data show that the autonomic control on heart rate and skin conductance are differentially modulated during BH, which could be related to a more pronounced effect on emotional control induced by the mental training to BH.